Consumer perception towards Bulk SMS for the marketing of various products/services of Robi Axiata Limited - Antu, Fahadul Islam (BRAC University, 2017)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2017.